Gastrointestinal stromal tumours (GISTs) with a thousand faces: atypical manifestations and causes of misdiagnosis on imaging. Issue 2 (February 2016) - Kim, S.W.; Kim, H.C.; Yang, D.M.; Won, K.Y.
Abstract : Gastrointestinal stromal tumours (GISTs) can lead to emergency situations, such as gastrointestinal bleeding, intestinal obstruction, and tumoural rupture with haemoperitoneum or peritonitis. In addition, if a GIST grows exophytically to a large size, it is often misdiagnosed as a tumour arising from adjacent organs. Sometimes, the atypical appearance of GISTs on imaging causes diagnostic confusion. In this article, we illustrate a variety of GISTs with atypical presentations and also discuss the important diagnostic clues for differentiating GISTs from other lesions.